2019
DOI: 10.1093/rheumatology/kez275
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric surgery and the incidence of rheumatoid arthritis – a Swedish Obese Subjects study

Abstract: Objective The aim of this study was to determine the effect of bariatric surgery on the incidence of RA in participants of the Swedish Obese Subjects (SOS) study. Methods The SOS is a longitudinal study aiming to assess the effect of bariatric surgery on mortality and obesity-related diseases. This report includes 2002 subjects with obesity who underwent bariatric surgery and 2034 matched controls; none of them had RA at base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 35 publications
(36 reference statements)
2
20
0
2
Order By: Relevance
“…www.scandjrheumatol.se .60, p = 0.01) ( Table 2). As previously shown (29), bariatric surgery was not associated with the incidence of the RA in the SOS study, whereas serum CRP levels and current or former smoking were associated with an increased risk for the disease (Table 2). Gender, ESR, and BMI were not risk factors for RA in this cohort of subjects with obesity.…”
Section: Baseline Characteristicssupporting
confidence: 56%
See 2 more Smart Citations
“…www.scandjrheumatol.se .60, p = 0.01) ( Table 2). As previously shown (29), bariatric surgery was not associated with the incidence of the RA in the SOS study, whereas serum CRP levels and current or former smoking were associated with an increased risk for the disease (Table 2). Gender, ESR, and BMI were not risk factors for RA in this cohort of subjects with obesity.…”
Section: Baseline Characteristicssupporting
confidence: 56%
“…In subjects with preclinical RA, auto-antibodies, chemokines, and cytokines are elevated in blood up to several years before the onset of the disease, suggesting an early activation of the immune system (33,36). CRP levels are also increased years before the diagnosis of RA (29,(33)(34)(35). CRP and adiponectin levels showed poor correlation, suggesting different mechanisms behind the regulation of these proteins (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The larger number of cohort studies in the present analysis contributed to more precise risk estimates, and enabled assessment of associations of other adiposity measures, such as waist circumference and BMI in early adulthood, with risk of rheumatoid arthritis. Some studies have suggested that bariatric surgery may improve symptoms in patients with rheumatoid arthritis 40,41 , however, www.nature.com/scientificreports/ a recent Swedish study found no significant association between bariatric surgery and the risk of developing rheumatoid arthritis (HR = 0.92, 95% CI 0.59-1.46), but statistical power to detect a moderate association may have been low and confidence intervals were wide 42 . The finding that high BMI in early adulthood (at age 18 years) was associated with an increased risk of rheumatoid arthritis might suggest that early life risk factors may be of importance in the aetiology of rheumatoid arthritis 43,44 .…”
Section: Discussionmentioning
confidence: 99%
“…Santos et al 31 enrolled 46 patients with obesity-related metabolic dysfunction and showed that gastric banding surgery resulted in a significant decrease in the inflammation process associated with adipose tissue loss. Interestingly, in a Swedish study followed up for 29 years, there was no association between bariatric surgery and the incidence of RA in obese patients 32 , which might demonstrate that bariatric surgery has no preventive effect on the occurrence of RA.…”
Section: Discussionmentioning
confidence: 94%